2015
DOI: 10.14419/ijh.v3i1.4479
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fingernail chromium, cadmium, and lead in tannery workers

Abstract: <p><strong>Purpose:</strong> To determine whether chromium, cadmium, and lead levels in human Fingernails reflected the exposure to workplace contamination in tanneries.</p><p><strong>Approach:</strong> 49 exposed tanning workers and 33 controls were monitored for fingernail levels of chromium, cadmium, and lead by graphite furnace and hydride atomic absorption spectroscopy.</p><p><strong>Results:</strong> The mean levels of fingernail chromium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…A meta-analysis [5] mentioned that household members who work in Pb contaminated environments or engage in particular hobbies can carry Pb to their houses through clothes or shoes they used at work. This supports the results of studies that found occupational exposure to be the most potent risk factor correlated with increased levels of chromium (Cr), cadmium (Cd), and Pb [27] . In this study, medical consultations revealed no symptoms related to chronic Pb toxicity whilst the concentrations are lower than those reported by Uruguayan children (4.2 ± 2.1 µg/dL) [37] .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…A meta-analysis [5] mentioned that household members who work in Pb contaminated environments or engage in particular hobbies can carry Pb to their houses through clothes or shoes they used at work. This supports the results of studies that found occupational exposure to be the most potent risk factor correlated with increased levels of chromium (Cr), cadmium (Cd), and Pb [27] . In this study, medical consultations revealed no symptoms related to chronic Pb toxicity whilst the concentrations are lower than those reported by Uruguayan children (4.2 ± 2.1 µg/dL) [37] .…”
Section: Resultssupporting
confidence: 86%
“…Survey results indicate that 46.7 % of CMA is exposed to indirect Pb contamination. This is probably happened due to the dust tracked into houses through the shoes and clothing of mining fathers [5, 27] . It seems that the majority of mothers from mining area (93.3 %) applied the traditional cosmetic product “khôl” to their children’s eyes during the first months of birth with statistically significant association (X 2 = 4.057; p = 0.044).…”
Section: Resultsmentioning
confidence: 99%
“…Both these heavy metals can originate from tanneries 26 . Moreover, some of the health hazards originating from ingestion of these elements (Cr 6+ and Cd) are of common nature.…”
mentioning
confidence: 99%